2021
DOI: 10.1111/opo.12780
|View full text |Cite
|
Sign up to set email alerts
|

Functional characteristics of glaucoma related arcuate defects seen on OCT en face visualisation of the retinal nerve fibre layer

Abstract: Purpose To assess continuity of perimetric defects corresponding to arcuate defects seen on optical coherence tomography (OCT) en face reflectance images of the retinal nerve fibre layer (RNFL) in patients with glaucoma. Methods Seven patients with glaucoma who had arcuate structural defects on OCT RNFL en face images were recruited. Static suprathreshold stimuli were presented along different meridians to localise perimetric defects in the corresponding hemifield. Then two contrasts, one 6 dB greater than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…En face RNFL reflectance maps have been found to have potentially good diagnostic ability for glaucomatous damage, [12][13][14][15][16][17][18][19][20] and good agreement with patterns of perimetric loss. 20,21 Because measured reflectance varies with the amount of light hitting the retina, measures of AC have been developed by using the ratio of measured reflectances for different layers within the retina. [22][23][24] The purpose of this study was to better understand the sources of variability in AC for en face RNFL reflectance maps from healthy eyes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En face RNFL reflectance maps have been found to have potentially good diagnostic ability for glaucomatous damage, [12][13][14][15][16][17][18][19][20] and good agreement with patterns of perimetric loss. 20,21 Because measured reflectance varies with the amount of light hitting the retina, measures of AC have been developed by using the ratio of measured reflectances for different layers within the retina. [22][23][24] The purpose of this study was to better understand the sources of variability in AC for en face RNFL reflectance maps from healthy eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories have reported that en face maps of RNFL reflectance show good potential for detecting glaucomatous damage, 12–19 and that by using fixed distances below the inner limiting membrane (ILM) the problems with normal between‐subject variability in the distance from the fovea to the arcades can be avoided 20,21 . Measured reflectance will be affected by factors that reduce the amount of light that reaches the tissue, such as shadows from blood vessels or floaters and changes in the position of the eye, but not by factors that affect RNFL thickness such as axial length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, en face images of RNFL reflectance have been found to reflect the spatial extent and pattern of perimetric defect, but not the depth of defect. 5,[19][20][21] If RNFL reflectance is to be useful for screening for those at greatest risk of visual impairment, then criteria with high specificity should have high sensitivity for identifying patients with deep perimetric defects. 23 The purpose of this study was to develop criteria with high sensitivity to these defects, with less emphasis on sensitivity to milder glaucomatous defects.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…[7][8][9] RNFL reflectance near the inner limiting membrane (ILM), which is less affected by the location of the arcades than RNFL thickness, has been found to have good sensitivity to glaucoma [10][11][12][13][14][15][16][17] and reasonable ability to predict the locations of glaucomatous perimetric defects. 5,[18][19][20][21] It has been proposed that RNFL reflectance may be at least as good as RNFL thickness in diagnostic efficiency for glaucoma, 22 and a recent study proposed that quantification of RNFL reflectance near the optic disc may make population-based screening for glaucoma feasible. 17 In clinical practice, false positive rates can be reduced by requiring the defect be detected by both imaging and perimetry.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%